2015
DOI: 10.1073/pnas.1508425112
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomic profiles enhance precision medicine for volunteers of normal health

Abstract: Precision medicine, taking account of human individuality in genes, environment, and lifestyle for early disease diagnosis and individualized therapy, has shown great promise to transform medical care. Nontargeted metabolomics, with the ability to detect broad classes of biochemicals, can provide a comprehensive functional phenotype integrating clinical phenotypes with genetic and nongenetic factors. To test the application of metabolomics in individual diagnosis, we conducted a metabolomics analysis on plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
156
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(158 citation statements)
references
References 63 publications
1
156
0
1
Order By: Relevance
“…Metabolomics has several advantages over genomics for the diagnosis of complex chronic disease and for the growing interest in precision medicine (5). First, fewer than 2,000 metabolites constitute the majority of the parent molecules in the blood that are used for cell-to-cell communication and metabolism, compared with 6 billion bases in the diploid human genome.…”
mentioning
confidence: 99%
“…Metabolomics has several advantages over genomics for the diagnosis of complex chronic disease and for the growing interest in precision medicine (5). First, fewer than 2,000 metabolites constitute the majority of the parent molecules in the blood that are used for cell-to-cell communication and metabolism, compared with 6 billion bases in the diploid human genome.…”
mentioning
confidence: 99%
“…4-Ethylphenylsulfate increased with sodium restriction and was the most strongly associated with change in sodium intake. This metabolite is produced by the gut microflora (11), and higher serum concentrations are associated with various health outcomes such as periodontal disease and lean body mass in animals or humans (12)(13)(14)(15)(16). 4-Ethylphenylsulfate is correlated with the consumption of soy products (17,18) and is elevated in the plasma of vegans compared with omnivores; a vegan diet increases concentrations of several products produced by the gut microbiota (19).…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that both diet and the microbiome mediate associations between metabolites and blood pressure (23). Although speculative, the effect of sodium restriction on the gut microbiome may contribute to the increases in 4-ethylphenylsulfate and possibly to changes in other metabolites (e.g., 4-hydroxyphenylpyruvate, indole-related metabolites, and isovalerate) produced by gut bacterial metabolism (11).…”
Section: Discussionmentioning
confidence: 99%
“…One way to go through the complexity of the data is by using metabolomics, able to precisely measure 2000 molecules in plasma. Metabolomics provides a real-time assessment of the phenotype, helps to unravel complex traits and to detect meaningful signals within the genome [7]. Novel technological innovations enable metabolomics to deliver signatures of disease and provide an integral tool for assessing mechanisms of drug action, thus expanding the boundaries of precision medicine and systems pharmacogenomics.…”
Section: Systems Pharmacogenomics and Mechanisms Of Drug Actionmentioning
confidence: 99%